Evaluating the Impact of Enhanced Recovery After Surgery (ERAS) on Postoperative Outcomes in Pancreatic Cancer Patients: A Historical Control Study - Wang, Jie; Agunod, Cyrelle D. (International Journal of Public Health and Medical Research, 2024)
Objective: This study evaluates the impact of the Enhanced Recovery After Surgery (ERAS) program on postoperative outcomes in patients undergoing pancreatic cancer surgery. It compares traditional perioperative care with ERAS-based interventions, focusing on key rehabilitation indicators such as postoperative intestinal function recovery, length of hospital stays, medical costs, and the incidence of complications. Methods: A total of 74 patients were studied, with 37 receiving traditional perioperative care and 37 managed under the ERAS protocol. Data collection included intraoperative indicators such as operation time, fluid input, blood loss, and postoperative recovery measures like first ambulation, pain scores, and complications. Results: The ERAS group demonstrated significantly faster recovery of gastrointestinal function, earlier mobilization, and reduced postoperative pain within the first 12 hours compared to the control group (p<0.05). The incidence of postoperative complications was lower in the ERAS group (13.51% vs. 37.84%, p=0.0166). Furthermore, the ERAS protocol led to a shorter length of hospital stay and lower total medical costs (p<0.0001). Conclusion: The implementation of the ERAS protocol for pancreatic cancer surgery significantly improves recovery outcomes, reduces complications, and lowers healthcare costs. These findings support the broader adoption of ERAS protocols in pancreatic cancer management to optimize clinical and economic outcomes.